Nobility criteria as a measure of Kafa'ah in marriage - Mesarah, Baiq Maya; Wathoni, Lalu Muhammad Nurul (Social Sciences Insights Journal, 2024)
During the royal era, it was common for marriages to require both partners to come from the nobility. This practice could be based on access to education and aspects of life worth that were more available to the nobility. So, a nobleman's marriage must be with a nobleman to get pure offspring. As in Indonesia, women with noble status are "pressured" according to unwritten rules to marry men from noble circles. This may be caused by the patriarchal system that regulates a person's nasab or lineage. Interestingly, the status of nobility has shifted and is no longer legitimized from aspects of life worthiness in the form of education, wealth, moral security, and position. This research uses the library research method, where researchers use literature materials such as books, articles, journals, magazines, and verses in the holy Koran related to this research. This research concludes that the jurists agree that the priority in kafa'ah is religion because religion is the axis for marriage, which brings the household to an eternal and harmonious ship. Nobility as a measure of kafa'ah has less and less relevance in the modern era; for some groups, this criterion is not the main thing. Even though it has a long history, and certain values attached to it, this criterion is no longer a priority when choosing a partner.